2023
DOI: 10.21608/ejnsr.2023.278179
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Electronic Mind Maps as a Teaching Strategy on Academic vitality, Self-Efficacy, and Achievement among Nursing Students

Abstract: Background: Electronic mind maps are one of the innovative learning approaches that help to improve students , achievement and self-efficacy. Aim: Examine the effect of using electronic mind maps as a teaching strategy on academic vitality, self-efficacy, and achievement among nursing students. Design: A quasi-experimental design with (pretest-posttests, case, and control groups) was utilized to conduct the study. Setting: The current study was conducted at the Faculty of Nursing, Menoufia University, Egypt. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…The findings of the present research showed that the use of concept maps provided high satisfaction of dents from teaching puerperal infection which is in accordance with studies of Freeman et al [32] Zaitseva et al [33], Hanani et al [16]. Elsayed Farid et al showed that 86% of the students in the electronic mind-mapping group were satisfied, while only 55% in the conventional group were satisfied [34].…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present research showed that the use of concept maps provided high satisfaction of dents from teaching puerperal infection which is in accordance with studies of Freeman et al [32] Zaitseva et al [33], Hanani et al [16]. Elsayed Farid et al showed that 86% of the students in the electronic mind-mapping group were satisfied, while only 55% in the conventional group were satisfied [34].…”
Section: Discussionsupporting
confidence: 91%